Limited health insurance coverage of injectable neurotoxins and fillers for gender affirmation: a cross-sectional study of Affordable Care Act silver and Medicaid plans - Karin Roszell, MD; Daniel Shumer, MD; Jeffrey Orringer, MD; Frank Wang, MD (Wolters Kluwer, 2024)
Background:. Injectable neurotoxins and fillers are potential options for facial gender affirmation for transgender/nonbinary patients. However, the largest barrier to access is cost/insurance coverage. Objective:. The purpose of this article is to assess the extent to which Affordable Care Act (ACA) silver plans and Medicaid policies cover gender-affirming injectable neurotoxin and filler procedures. Methods:. A cross-sectional study of all ACA silver plans and Medicaid policies was performed from June 22 to August 15, 2021. Plan-specific certificates of coverage, clinical policies of insurance providers, and Medicaid documents were evaluated. Results:. A total of 915 plans were reviewed (864 ACA silver plans and all 51 Medicaid policies). None potentially covered neurotoxins. Only 72 (71 ACA and 1 Medicaid) potentially covered fillers, specifically collagen injections and lipofilling. Coverage required demonstration of medical necessity or significant variation of physical appearance from the patient's experienced gender. However, of the 71 ACA plans, 69 outlined cosmetic exclusions, possibly nullifying this coverage. Limitations:. Data were sourced from publicly available online information in 2021. Additionally, we were unable to confirm explicit coverage of these procedures with insurance companies. Conclusion:. The majority of ACA silver and Medicaid plans did not cover gender-affirming neurotoxin or filler procedures, limiting access to this gender-affirming care.